Implementation of Management of COVID-19 Prevention and Control at PT. X - Fathul Masruri Syaaf; Robiana Modjo; Fatma Lestari (International Journal Labs, 2023)
The Coronavirus Disease (COVID-19) pandemic has become a major ongoing global economic crisis, including in the construction sector. To recover the economy in line with Government Policy, PT. X implements the Management of COVID-19 Prevention and Control because Company realizes protecting workers' health is a top priority. This study aims to provide an overview of management COVID-19 prevention and control implementation and recommendations and effective strategies for improvement. The research design used was a cross-sectional study using an online interview and secondary data. Data will be analyzed using SWOT Analysis. The study only focused on activities and working conditions at PT. X. This study uses qualitative methods. The information was collected through in-depth interviews with key informants and supporting documents used in the data triangulation process—COVID-19 prevention and control measures implemented at PT. X refers to the company, local government, and central government regulations and policies. The company has implemented several programs during PPKM. In general, the implementation of the COVID-19 health protocol at PT X has been exemplary. Management always emphasizes the commitment of all levels to understand the COVID-19 pandemic, transmission routes, and control and prevention measures to minimize the significant impact on the company's business operations.